Contemporary dilemnas and radical defences : models of the church in the theologies of Paul Tillich (1886-1965) and Juan Luis Segundo (1925-1998). - Williamson, Kenneth B. (University of Ottawa (Canada), 2000)
Paul Tillich and Juan Luis Segundo have separately advocated changes in Christian thinking which, if accepted, would gradually develop new models of the Church, both in the perception of its members and of society generally. At the level of theological revision of belief the proposals vary considerably. Tillich elaborated a systematic and philosophical theology containing a synthesis of elements both of contemporary and of traditional Christian thought. His theology presented a radical challenge to traditional theism. His concept of the Church, however, as the institutional and cultural manifestation of religious meaning retained an emphasis on sacramentality and mission in society intended to ensure continuity of what he saw as a sacred community. At the same time he extended the concept and intuition of such a community within the Church to a latent one outside the institution. After an earlier emphasis on religious socialism as part of the mission of the Church he turned to concern for what has been called the ontological security of the individual in the face of deep anxiety. Segundo has insisted on the legitimacy of what he calls the liberation of dogma by new methods of interpretation enabling the Church to respond to the most urgent needs of contemporary society. In company with other liberation theologians he has identified those needs as release from the alienation and injustice created by the powerful economic structures of capitalism. Unlike most other liberation theologians he is convinced that such change will come about so far as the Church is concerned only through the efforts of a minority vanguard working within the Church in order to change the mentality of Church leaders with respect to its obligation to advance the Kingdom of God in history. He has not presented an alternative theological system so much as he has insisted that Scriptual warranty and Christian experience point to that obligation and that secular ideologies can be used as a means to fulfil that obligation. The influence which such trends in theology could exert on the churches would probably be apparent in the following ways: (1) less emphasis on formal acceptance of inherited creeds as a condition of membership; (2) acceptance of pluralism in theological analysis and expression; (3) a continuing ecumenical convergence; (4) erosion of claims to divine authority inherent in Church and Scripture but with maintenance of firm institutional governance; (5) openness to processes of selective secularization with regard to contemporary social issues in the field of human rights for example; (6) a considerably increased role for the laity with an emphasis on their continuing education and (7) an insistence on the obligation to judge social and political issues combined with avoidance of a role as a direct political agent. Since this is an analysis of the eventual impact of ideas on inherited bodies of thought and on the functioning of an institution, the points listed above are conjectural. On the basis of a pre-supposition that the current malaise within the institution has its roots in anxiety about adaptation within modern and secular culture, the principal contribution of these two theologians is to make the point that the creedal and theological superstructure can change without undermining the stability and vitality of the Church.
Keywords: Religion, General.